2020
DOI: 10.1016/j.ijid.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of yellow fever, dengue, West Nile and chikungunya viruses in children in Teso South Sub-County, Western Kenya

Abstract: Background: Arboviruses often cause widespread morbidity in children in endemic regions. Data on the burden of arboviruses in Kenyan children are limited. Objectives: This study was performed to determine the seroprevalence of yellow fever (YFV), dengue (DENV), West Nile (WNV), and chikungunya (CHIKV) viruses among children 1-12 years of age at two health facilities in Teso South Sub-County in Western Kenya. Methods: In a hospital-based cross-sectional survey, a questionnaire was used to collect sociodemograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The finding of the current study indicated that 7.4% of febrile patients were seropositive for by WNV-specific IgG and the finding was comparable with the study conducted in Ilorin, Nigeria that was 7.5%. 25 However, the higher rates were reported by several studies from asymptomatic and febrile patients: like10.2% and 9.6% in Kenya, 24,26 73.2% and 80.1% in Nigeria, 27,28 27.9% in Ghana, 29 27.2% in Gabon with different prevalence rate in diverse ecosystems like 23.7% in forested regions, 21.8% in savanna and 64.9% in the lakes region, 30 and 59% in the Democratic Republic of Congo. 31 On the other hand, the finding of this study was higher than the studies conducted in the South Omo zone, Southern Ethiopia, 23 Spain, 32 United States, 33 Greek, 34 and Libya.…”
Section: Discussionmentioning
confidence: 94%
“…The finding of the current study indicated that 7.4% of febrile patients were seropositive for by WNV-specific IgG and the finding was comparable with the study conducted in Ilorin, Nigeria that was 7.5%. 25 However, the higher rates were reported by several studies from asymptomatic and febrile patients: like10.2% and 9.6% in Kenya, 24,26 73.2% and 80.1% in Nigeria, 27,28 27.9% in Ghana, 29 27.2% in Gabon with different prevalence rate in diverse ecosystems like 23.7% in forested regions, 21.8% in savanna and 64.9% in the lakes region, 30 and 59% in the Democratic Republic of Congo. 31 On the other hand, the finding of this study was higher than the studies conducted in the South Omo zone, Southern Ethiopia, 23 Spain, 32 United States, 33 Greek, 34 and Libya.…”
Section: Discussionmentioning
confidence: 94%
“…Overall, evidence about dengue in Africa is limited ( Amarasinghe et al, 2011 ) and is mostly from outbreak investigations and retrospective testing of existing serum banks from other studies ( Ellis et al, 2015 , Obonyo et al, 2018 ), although, among African countries, Kenya has relatively more evidence ( Ellis et al, 2015 , Obonyo et al, 2018 , Konongoi et al, 2016 , Masika et al, 2020 , Inziani et al, 2020 , Ochieng et al, 2015 ). Our data showed that dengue infection is an important cause of non-malarial febrile illness in patients seeking care at public health facilities and adds to the available literature on the endemicity of dengue in Mombasa.…”
Section: Discussionmentioning
confidence: 99%
“…The study found IgG seroprevalence to be 3.5% in Nairobi and 14.6% in Taita–Taveta, confirming local transmission in this part of rural Kenya ( Masika et al, 2020 ). Between 2010 and 2011, a hospital-based cross-sectional survey was conducted in Western Kenya among children aged 12 years and under ( Inziani et al, 2020 ). Of 656 children, 1%, 9%, and 20% tested positive by indirect ELISA for DENV 1, 2, and 3, respectively ( Inziani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks of CCHF (Dunster et al, 2002) and RVF (WHO, 2018) have been reported before in Western Kenya, and there is serological evidence of circulation of chikungunya, yellow fever, West Nile, and RVF viruses (Cook et al, 2017;Inziani et al, 2020;Mease et al, 2011;Nyaruaba et al, 2019). While reports on the occurrence of zoonotic vector-borne bacteria are scant, the high prevalence of malaria in Western Kenya results in under-investigation of other causes of febrile illnesses.…”
Section: Introductionmentioning
confidence: 99%